Hypolobocera den tata sp. nov.: A new freshwater crab (Crustacea: Brachyura: Pseudothelphusidae) from the Cordillera Occidental, Colombia - von Prahl, Henry (1987)
A new species of Pseudothelphusidae is described from the Cordillera Occidental of Colombia. Hypolobocera dentata sp. nov. adds a fourth species to group IV. lts gonopod resembles that of H. chocoensis and H. malagueña, but differs in the presence of spines on the flange of the apical border of the gonopod and by the presence of tubercles on the surface and border of the lateral lobe.